Zinc Essentiality, Toxicity, and Its Bacterial Bioremediation: A Comprehensive Insight - Hussain, Sarfraz; Khan, Maryam; Sheikh, Taha Majid Mahmood; Mumtaz, Muhammad Zahid; Chohan, Talha Ali; Shamim, Saba; Liu, Yuhong (Frontiers in Microbiology, 2022)
Zinc (Zn) is one of the most abundantly found heavy metals in the Earth’s crust and is reported to be an essential trace metal required for the growth of living beings, with it being a cofactor of major proteins, and mediating the regulation of several immunomodulatory functions. However, its essentiality also runs parallel to its toxicity, which is induced through various anthropogenic sources, constant exposure to polluted sites, and other natural phenomena. The bioavailability of Zn is attributable to various vegetables, beef, and dairy products, which are a good source of Zn for safe consumption by humans. However, conditions of Zn toxicity can also occur through the overdosage of Zn supplements, which is increasing at an alarming rate attributing to lack of awareness. Though Zn toxicity in humans is a treatable and non-life-threatening condition, several symptoms cause distress to human activities and lifestyle, including fever, breathing difficulty, nausea, chest pain, and cough. In the environment, Zn is generally found in soil and water bodies, where it is introduced through the action of weathering, and release of industrial effluents, respectively. Excessive levels of Zn in these sources can alter soil and aquatic microbial diversity, and can thus affect the bioavailability and absorption of other metals as well. Several Gram-positive and -negative species, such as Bacillus sp., Staphylococcus sp., Streptococcus sp., and Escherichia coli, Pseudomonas sp., Klebsiella sp., and Enterobacter sp., respectively, have been reported to be promising agents of Zn bioremediation. This review intends to present an overview of Zn and its properties, uses, bioavailability, toxicity, as well as the major mechanisms involved in its bioremediation from polluted soil and wastewaters.